The aqueous electrophoretic deposition (EPD) of diamond-diamond laminates - Džepina, Branislav (My University, 2013)
It is known that the wear resistance of polycrystalline diamond (PCD) is inversely proportional to the particle size of the diamond powder which is to be sintered. Fracture toughness on the other hand is directly proportional to the particle size of the starting powder. Therefore, fracture toughness and wear resistance work antagonistically. A layered PCD structure made by using powders with a relatively small particle size could result in a more fracture resistant cutter while still retaining desirable wear properties. The focus of this project was to determine if a layered diamond structure could be made by electrophoretic deposition (EPD) and whether the sintered laminate showed crack deflection during fracture. The aqueous EPD of a diamond/diamond laminate with two alternating grades of diamond was investigated. Diamond particles, 0.5μm and 2μm in size, were deposited in an alternating manner onto tungsten carbide substrate. The layered diamond deposit was sintered with the carbide substrate in a high-pressure, high-temperature press. The sintered deposit was examined for evidence of alternating residual stresses. Differences of cobalt content in the 0.5 and 2μm layers were observed by EDS and image analysis. The sintered diamond laminate was subjected to three-point bending until fracture. Although the sample had demonstrated only minimal crack deflection during the bend test, further analysis revealed that a sintering cooling crack showed evidence of crack deflection.